Aligning Global Sustainability Governance with Chinese IPE: A Model for Global Citizenship Education - Li, Xinrui; Bao, Hui; Hu, Dandan (INTI International University, 2025)
This study examines the integration of global sustainability into China's ideological and political education (IPE) curriculum, responding to the urgency of global environmental crises and UNESCO's call for transformative education. Employing a sequential mixed-methods approach, it investigates how the "community with a shared future for mankind" and UN Sustainable Development Goals (SDGs) can be systematically embedded in IPE to enhance students' global environmental literacy and political participation in environmental governance. The "Ideology-Governance-Action" (IGA) Tridimensional Curriculum Model, implemented at Southwest Jiaotong University Hope College, aligns learning objectives with the Paris Agreement and China's "ecological red line" policies via case-based learning, simulated UN climate negotiations, and NGO-led service-learning projects. Post-reform outcomes—72% increased SDG awareness up from 28% and 45% extracurricular sustainability engagement up from 15%—coupled with qualitative evidence of students critiquing "Western-centric" narratives and proposing China-led "ecological civilization" solutions, demonstrate feasibility and effectiveness. While faculty face interdisciplinary collaboration and resource challenges, the model offers emerging-economy higher education institutions (HEIs) a replicable framework to balance national sovereignty and global citizenship, with implications for curriculum design, faculty development, and student-led sustainability initiatives.